2018
DOI: 10.21767/1791-809x.1000566
|View full text |Cite
|
Sign up to set email alerts
|

Tabletop Exercise on Mass Casualty Incident Triage, Does it Work?

Abstract: Background: The triage is the first step in medical hierarchy for better management before treatment and transport in mass casualty incident (MCI). Therefore, an accurate, valid and timely triage will safe life and limbs, especially, when done by expert and experienced staff in MCI triage. This study planned to evaluate the MCI triage skills of the medical staff like doctors and nurses at Hamad General Hospital Emergency Department (HGH ED). They were provided a table top exercise (TTX) about MCI triage to imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 10 publications
0
19
0
1
Order By: Relevance
“…Fig. 6 shows how the patients are prioritized based on the sensed data and GCS calculated by the given instructions of Table 4 [25] , [26] .…”
Section: Proposed Schemementioning
confidence: 99%
“…Fig. 6 shows how the patients are prioritized based on the sensed data and GCS calculated by the given instructions of Table 4 [25] , [26] .…”
Section: Proposed Schemementioning
confidence: 99%
“…Nurses' education on natural disasters fosters their motivation and positively affects their healthcare provision [18]. Kaplan et al demonstrated the positive effect of these simulation exercises on nursing students [19].…”
Section: Plain Language Summarymentioning
confidence: 99%
“…Despite the availability of various teaching methods, their efficacy and efficiency still need to be studied [18].Therefore, given the numerous teaching methods, it is highly important to identify the most effective pedagogic procedure with the highest efficacy for learners. Consequently, this study compared the effects of lecturing and tabletop exercise methods on the level of nurses' preparedness against natural disasters at a hospital in Yazd, City, Iran, in 2017.…”
Section: Plain Language Summarymentioning
confidence: 99%
“…In Sarpy, Warren, Kaplan, Bradley, and Howe's and Khan's, both studies used role‐based tabletop exercises. In each study, the healthcare professionals were functioning in their practice roles, making individual decisions to solve the scenario practice problem, response to an outbreak of severe acute respiratory syndrome and patient triage, respectively.…”
Section: Recent Healthcare Literature Using Tabletop Exercisesmentioning
confidence: 99%